ปัจจัยที่มีความสัมพันธ์กับพฤติกรรมการตรวจเต้านมด้วยตนเองในสตรีไทย เขตอำเภอองครักษ์ จังหวัดนครนายก - บูรณะเรืองโรจน์(Sirinoot Buranaruangrote) สิรินุช (Journal of Behavioral Science for Development, 2016)
(Factors related to breast self examination behavior in Thai women living in Ongkharak District Nakhonnayok ) Abstract This cross-sectional study is aimed to explore the relationships of predisposing factors as age, educational attainment, and breast cancer knowledge and breast self examination (BSE) and reinforcing factor as health care provider’s recommendations to perform BSE with BSE behavior in Thai women living in Ongkharak district Nakhonnayok Thailand. The PRECEDE–PROCEED planning model by Green & Kreuter (1991) was used as a theoretical framework. The participants were 400 Thai women who sought treatment at out-patient department of university hospital in Ongkharak district Nakhonnayok. The participants were recruited based on the criteria previously set. Data were collected by means of a set of 3 questionnaires: 1) demographic data, 2) breast cancer knowledge and BSE, and 3) health care provider’s recommendations to perform BSE and BSE behavior. Percentage, Chi-square and Contingency Coefficient were used for data analysis. The results revealed that age, educational attainment, breast cancer knowledge and BSE, and health care provider’s recommendations to perform BSE were significantly related to BSE behavior in Thai women living in Ongkharak district Nakhonnayok as respectively (p <.001), (p <.05), (p <.05) and (p <.001). Based on these findings, to make Thai women aware of and have regular of BSE behavior it is recommended that nurses should give advice, care, support, and encourage all Thai women from aged 20 years about breast cancer knowledge and BSE training correctly and consistently. The BSE training should be repeated at intervals regularly and continuously. Keywords: Breast self examination, Thai women, Ongkharak, PRECEDE–PROCEED planning model